PENGARUH PELATIHAN MENJAHIT BLK TERHADAP PEMBERDAYAAN EKONOMI MASYARAKAT KAMPUNG PANGGULAN - Bintang Aditya Ramadhan; Ani Safitri (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This study aims to examine the influence of sewing training organized by the Balai Latihan Kerja (BLK) on the economic empowerment of the community in Kampung Panggulan. The research employed a qualitative approach to gain an in-depth understanding of the training implementation process, participants’ experiences, and the economic impacts perceived after joining the program. Data were collected through triangulation techniques, including questionnaires, observations, interviews, and documentation. The findings show that the BLK sewing training received positive responses from participants. The training materials were considered relevant to community needs, the learning methods emphasized practical activities, and instructors provided effective guidance. The results indicate improvements in participants’ sewing skills, work motivation, and self-confidence. Moreover, the training contributed to increased productivity, the emergence of new income sources, and greater economic independence among participants. Several participants utilized their skills for home-based businesses, sewing services, and collaborative economic activities within the community. These findings support the human capital theory, which emphasizes that investment in skills development can enhance productivity and income. Overall, the BLK sewing training can be considered an effective non-formal education program in promoting sustainable community economic empowerment.